1982
DOI: 10.1016/0035-9203(82)90161-4
|View full text |Cite
|
Sign up to set email alerts
|

Yellow fever and Zika virus epizootics and enzootics in Uganda

Abstract: Data of monkey serology are presented which, together with past evidence, support the view that yellow fever (YF) virus circulates in its primary sylvan host populations, i.e., forest monkeys, in an enzootic state in Bwamba County in western Uganda but as series of epizootics in the forest-savanna mosaic zone of central Uganda. Evidence of an epizootic of Zika virus at the Zika Forest near Entebbe is described which occurred in two episodes, the first (in 1969) apparently following the build-up of non-immune m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
141
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(144 citation statements)
references
References 26 publications
1
141
0
2
Order By: Relevance
“…Their progeny were viral infected as well and viral RNA was detected in several progeny tissues (salivary glands, ovaries, testes, head, fat bodies, and midgut) [ 27 ]. Previously, TOT had been proposed as a mechanism contributing to the spread of Zika and yellow fever viruses in Uganda [ 28 ]. Thus, TOT should be studied in greater detail and therapies developed to combat the fail-safe mechanism that allows seasonal survival of arboviruses.…”
Section: Mosquitoesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their progeny were viral infected as well and viral RNA was detected in several progeny tissues (salivary glands, ovaries, testes, head, fat bodies, and midgut) [ 27 ]. Previously, TOT had been proposed as a mechanism contributing to the spread of Zika and yellow fever viruses in Uganda [ 28 ]. Thus, TOT should be studied in greater detail and therapies developed to combat the fail-safe mechanism that allows seasonal survival of arboviruses.…”
Section: Mosquitoesmentioning
confidence: 99%
“…This contradicted the hypothesis that subsequent YF epizootics would be subdued by Zika virus infections in nature for red-tail monkeys. Two factors important for further study of fl avivirus mosquito are transovarial and phlebotomine sand-fl y transmission [ 28 ].…”
Section: Monkeysmentioning
confidence: 99%
“…Both urban (Grard et al, 2014) and sylvatic (Berthet et al, 2014) transmission have been demonstrated. Epizootics occur in monkeys (McCrae & Kirya, 1982), but it is unclear as yet whether primates are an obligatory reservoir in the transmission cycle in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In 1947 the virus was first isolated from a febrile sentinel rhesus monkey (Rhesus 766) placed in a cage in the Zika forest of Uganda under the observation of Rockefeller Foundation's program for research on jungle yellow fever [2] while a second isolation was done from the mosquito Aedes africanus followed at the same site in January 1948 [1]. Most likely it is thought that, ZIKV maintained a sylvatic cycle involving non-human primates and several Aedes species (Ae.africanus, Ae.aegypti and others) as mosquito vectors [2][3][4], with cyclic epizootics in monkeys reported in Uganda [5][6][7][8]. Humans are get infected by infective mosquito bites, however recent report suggests that there is a possibility of secondary sexual transmission [9].…”
Section: Introductionmentioning
confidence: 99%